Integrated design for assembly methodology for electrical machines with distributed wound coils - Ogilvie, Duncan (2018)
Modern European manufacturing companies are facing increasing competition from cheaper imported goods. This is especially true for manufacturers of synchronous alternators and induction motors. To ensure they remain competitive into the future, much emphasis is placed on developing higher quality products by using modern, efficient assembly technologies. However, within the alternator industry, distributed wound electrical machines have not experienced any improvement in manufacturing quality or efficiency over the last two decades. This can be directly attributed to the highly constrained electrical design requirements of the stator core, the failure of companies to systematically implement design for manufacture and assembly methodologies, and the lack of concurrent engineering and communication within the overall design process. This thesis focuses on the development of an integrated design for assembly methodology for electrical machines with distributed wound coils. This work presents a novel design for assembly methodology which enables systematic concept design embodiment creation, evaluation and optimisation. The process ensures that all products are developed for assembly ease whilst not neglecting any other important design criteria. This work presents a systematic method of directly linking the product design to the assembly requirements by developing a design synthesis approach. This enables the assembly system to be specified and have its architecture modeled and evaluated – allowing the product and process to be developed concurrently. Finally, this thesis presents an information infrastructure model which captures, classifies and structures all important design information. This supports the overall concurrent engineering process by ensuring information is available centrally and is traceable throughout the whole design process.